2017
DOI: 10.1186/s12862-017-1016-x
|View full text |Cite
|
Sign up to set email alerts
|

Hostplant change and paleoclimatic events explain diversification shifts in skipper butterflies (Family: Hesperiidae)

Abstract: Background: Skippers (Family: Hesperiidae) are a large group of butterflies with ca. 4000 species under 567 genera. The lack of a time-calibrated higher-level phylogeny of the group has precluded understanding of its evolutionary past. We here use a 10-gene dataset to reconstruct the most comprehensive time-calibrated phylogeny of the group, and explore factors that affected the diversification of these butterflies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 96 publications
9
60
1
Order By: Relevance
“…For Hedylidae, only the study by Heikkilä et al (2012) had an estimate for the crown age, whose mean age was 45.3 Ma, which is older than our result (32.8, 95%CI=23.4–43.6). The age of Hesperiidae (65.2, 95%CI=55.8–78.1) was similar to Wahlberg et al (2013) and Heikkilä et al (2012), but much younger than Sahoo et al (2017) with an estimate of 82 Ma. Pieridae is the family that showed highest variation in age estimates among different studies.…”
Section: Resultsmentioning
confidence: 83%
“…For Hedylidae, only the study by Heikkilä et al (2012) had an estimate for the crown age, whose mean age was 45.3 Ma, which is older than our result (32.8, 95%CI=23.4–43.6). The age of Hesperiidae (65.2, 95%CI=55.8–78.1) was similar to Wahlberg et al (2013) and Heikkilä et al (2012), but much younger than Sahoo et al (2017) with an estimate of 82 Ma. Pieridae is the family that showed highest variation in age estimates among different studies.…”
Section: Resultsmentioning
confidence: 83%
“…Feeding on nutrient-deficient grasses, sedges and palms (34) leads to a prolonged caterpillar stage and may increase the likelihood of oxidative damage that would be mitigated by additional catalases. Apparently switching to monocot feeding was an evolutionarily successful innovation that resulted in explosive speciation in both satyrs and grass-skippers (35). They became the most species-rich phylogenetic groups among American butterflies, and their parallel diversifications of catalases are intriguing.…”
Section: Fig 1 Ultra-conserved Genomic Elements (Uce) In Butterfly mentioning
confidence: 99%
“…A recent study on Hesperiidae butterflies reported a strong increase in diversification coincident with a switch from dicot-feeders to monocot-feeders (Sahoo, Warren, Collins, & Kodandaramaiah, 2017). As postulated for Hesperiidae, the emergence of open grasslands and global temperature decrease may have affected diversification in the Sclerotiniaceae.…”
Section: Discussionmentioning
confidence: 89%